Multilayer composite proton exchange membrane for direct methanol fuel cell

The multilayer composite proton exchange membrane addresses methanol permeability and swelling issues in direct methanol fuel cells by using perfluorosulfonic acid resin and ePTFE absorption layers, enhancing efficiency and enabling cost-effective mass production without pretreatment.

CN222214216UActive Publication Date: 2024-12-20JIANGSU YUANHYDROGEN NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202421165347.7
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2024-12-20
Estimated Expiration
2034-05-27

AI Technical Summary

Technical Problem

The existing proton exchange membranes in direct methanol fuel cells suffer from high methanol permeability, leading to reduced battery performance, increased polarization, and difficulty in mass production due to swelling and the need for protonation pretreatment.

Method used

A multilayer composite proton exchange membrane composed of perfluorosulfonic acid resin layers and ePTFE absorption layers, with a modified perfluorosulfonic acid resin layer on the anode side, reduces methanol permeability and swelling, enabling direct coating and roll-to-roll production.

Benefits of technology

The multilayer membrane enhances methanol utilization efficiency, improves power density, facilitates mass production, and eliminates the need for protonation pretreatment, thereby increasing production efficiency and output performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222214216U_ABST
    Figure CN222214216U_ABST
Patent Text Reader

Abstract

The utility model discloses a multilayer composite proton exchange membrane for a direct methanol fuel cell, which comprises at least two perfluorinated sulfonic acid resin layers and ePTFE (enhanced polytetrafluoroethylene) absorption layers, the perfluorinated sulfonic acid resin layers and the ePTFE absorption layers are alternately attached and connected, a modified perfluorinated sulfonic acid resin layer is attached below the lowest ePTFE absorption layer, and the modified perfluorinated sulfonic acid resin layer is attached below the ePTFE absorption layer. The perfluorinated sulfonic acid resin layer on the uppermost layer is used as a cathode side, and the modified perfluorinated sulfonic acid resin layer is used as an anode side. According to the mode, the multi-layer composite proton exchange membrane for the direct methanol fuel cell is formed by combining the perfluorinated sulfonic acid resin layer, the ePTFE absorption layer and the modified perfluorinated sulfonic acid resin layer, so that the methanol permeability is reduced, the swelling ratio is reduced, and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to a field, in particular to a multilayer composite proton exchange membrane for a direct methanol fuel cell. Background Art

[0002] Direct methanol fuel cell (DFMC) has significant advantages such as environmental friendliness, high specific energy density, simple structure, and easy fuel portability, which has attracted widespread attention from researchers. At present, the most critical problem of proton exchange membrane in DMFC is methanol penetration due to diffusion and electrical permeation resistance. Methanol can penetrate into the cathode through PEM, resulting in mixed potential at the cathode, reducing the voltage of the battery, and greatly increasing the polarization and poisoning of the cathode electrode. These conditions will reduce the battery performance by 20%. Therefore, how to avoid methanol penetration has become one of the main directions to break through the technical bottleneck of DMFC.

[0003] Direct conductive polymer fuel cells can be divided into proton exchange membrane fuel cells, direct methanol fuel cells, direct ethanol fuel cells, direct formic acid fuel cells and direct dimethyl ether fuel cells according to the different anode fuels. As a representative of low-temperature fuel cells, direct methanol fuel cells (DFMC) have broad application prospects in portable power sources, light electric vehicles, small civilian power sources and other fields due to their simple structure, abundant raw material storage, safe operation, easy fuel portability and convenient charging. At the same time, it is also a low-temperature fuel cell that is currently being studied more.

[0004] In DMFC, the proton exchange membrane (PEM) used is generally a thicker homogeneous perfluorosulfonic acid resin membrane from Dupont. The methanol permeability of Nafion membrane is very high, up to 40wt.% of the total. This problem is the most critical problem of Nafion membrane in DMFC, mainly due to diffusion and electrical permeation resistance. Methanol can penetrate into the cathode through the Nafion membrane, resulting in a mixed potential at the cathode, reducing the voltage of the battery, and greatly increasing the polarization and poisoning of the cathode electrode. Affected by methanol permeation, the methanol fuel concentration used in DMFC is generally maintained below 4 mol / L. Compared with other commercial batteries, in order to make it competitive, the methanol concentration used needs to be increased to above 9 mol / L to effectively improve the energy density of DMFC. In addition to the above-mentioned problems of Nafion membrane in DMFC, there are two other issues to consider when using Nafion membrane in DMFC: (1) The swelling rate of Nafion membrane is as high as 15%, which makes it difficult to mass produce the core component of DMFC, membrane electrode assembly (MEA). In the process of preparing MEA, Nafion has a high swelling rate, and it is difficult to keep the Nafion membrane flat. It is difficult to achieve mass production using roll-to-roll or direct coating. In addition, the catalyst loading is several milligrams per square meter, which makes the catalyst coated membrane (CCM) prone to cracking, thus affecting battery performance. (2) Nafion membrane requires a protonation pretreatment process, which significantly reduces the production efficiency of MEA. Therefore, it is very important to develop a proton exchange membrane that can greatly reduce methanol permeability and swelling rate and does not require pretreatment.

[0005] Patent CN202410271616.6 discloses a multi-layer gradient composite proton exchange membrane and its preparation method, which generally describes that the ePTFE absorption layer, high-additive perfluorosulfonic acid resin solution, low-additive perfluorosulfonic acid resin solution and additive-free perfluorosulfonic acid resin solution are coated and rolled to form a multi-layer gradient composite proton exchange membrane, which can effectively avoid the chemical degradation of the multi-layer gradient ion polymer layer outside the proton exchange membrane and ensure the proton conduction ability of the proton exchange membrane, and solve the problems of poor proton conductivity and chemical durability of the proton exchange membrane during the operation of the proton exchange membrane fuel cell. However, the multi-layer gradient composite proton exchange membrane needs to be configured with a variety of perfluorosulfonic acid resin solutions during the quality assurance process, the process is complicated, and the production efficiency is low. Summary of the invention

[0006] The main technical problem solved by the utility model is to provide a multilayer composite proton exchange membrane for a direct methanol fuel cell, which is composed of a perfluorosulfonic acid resin layer, an ePTFE absorption layer and a modified perfluorosulfonic acid resin layer, thereby reducing methanol permeability, reducing swelling rate and improving production efficiency.

[0007] In order to solve the above technical problems, a technical solution adopted by the utility model is: to provide a multilayer composite proton exchange membrane for a direct methanol fuel cell, comprising at least two layers of perfluorosulfonic acid resin layers and ePTFE absorption layers, the perfluorosulfonic acid resin layers and the ePTFE absorption layers are alternately bonded and connected, a modified perfluorosulfonic acid resin layer is bonded under the bottom ePTFE absorption layer, the top perfluorosulfonic acid resin layer serves as the cathode side, and the modified perfluorosulfonic acid resin layer serves as the anode side.

[0008] In a preferred embodiment of the present invention, the ePTFE absorption layer is formed by laminating an ePTFE microporous membrane on the fluorosulfonic acid resin layer.

[0009] In a preferred embodiment of the present invention, the thickness of the ePTFE absorption layer is.

[0010] In a preferred embodiment of the present invention, the thickness of the perfluorosulfonic acid resin layer is.

[0011] In a preferred embodiment of the present invention, the thickness of the modified perfluorosulfonic acid resin layer is.

[0012] The beneficial effects of the utility model are as follows: the multilayer composite proton exchange membrane used in the direct methanol fuel cell of the utility model reduces the methanol permeability, improves the methanol utilization efficiency, thereby improving the power density of DMFC, reduces the swelling rate, and can realize mass production of direct coating / roll-to-roll process, ensures the batch production of MEA and the output performance of DMFC, does not need protonation pretreatment, and improves the production efficiency of MEA. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] In order to more clearly illustrate the technical solutions in the embodiments of the present utility model, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present utility model. For those skilled in the art, other drawings can be obtained based on these drawings without creative work, among which:

[0014] Figure 1 This is a schematic diagram of the structure of a multilayer composite proton exchange membrane for a direct methanol fuel cell of the utility model;

[0015] Figure 2 is a comparison table of the physical and electrochemical properties of the proton exchange membranes of Examples 1-3 and the proton exchange membranes of Comparative Examples 1-3;

[0016] The components in the accompanying drawings are marked as follows: 1. perfluorosulfonic acid resin layer, 2. ePTFE absorption layer, 3. modified perfluorosulfonic acid resin layer. DETAILED DESCRIPTION

[0017] The technical scheme in the embodiment of the utility model will be described clearly and completely below. The structure, proportion, size, etc. illustrated in the drawings of this specification are only used to match the content disclosed in the specification, so that people familiar with this technology can understand and read, and are not used to limit the limiting conditions that can be implemented in the utility model, so they have no technical substantive significance. Any modification of the structure, change of the proportional relationship or adjustment of the size, without affecting the effect that can be produced by the utility model and the purpose that can be achieved, should still fall within the scope of the technical content disclosed in the utility model. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and so on quoted in this specification are only for the convenience of narration, and are not used to limit the scope that can be implemented. The change or adjustment of its relative relationship should also be regarded as the scope that can be implemented in the utility model without substantially changing the technical content.

[0018] See also Figure 1 and Figure 2 A multilayer composite proton exchange membrane for a direct methanol fuel cell includes two layers of perfluorosulfonic acid resin layers 1 and two layers of ePTFE absorption layers 2. The uppermost perfluorosulfonic acid resin layer 1 is formed by coating a perfluorosulfonic acid resin solution on a release film, and the release film can be peeled off after the finished product is made. The ePTFE absorption layer 2 is formed by laminating the ePTFE microporous membrane on the fluorosulfonic acid resin layer. The thickness of the ePTFE absorption layer 2 is. The porosity of the ePTFE microporous membrane is greater than 80%.

[0019] The thickness of the release film is 0-250 μm, and the release film adopts any one of conventional release polyethylene terephthalate (PET), release polyethylene naphthalate (PEN), release polypropylene film (PP) or release polyethylene film (PE).

[0020] The perfluorosulfonic acid resin layer 1 and the ePTFE absorption layer 2 are alternately bonded and connected, and a modified perfluorosulfonic acid resin layer 3 is bonded below the bottom ePTFE absorption layer 2, and the top perfluorosulfonic acid resin layer 1 serves as the cathode side, and the modified perfluorosulfonic acid resin layer 3 serves as the anode side. The thickness of the perfluorosulfonic acid resin layer 1 is . The thickness of the modified perfluorosulfonic acid resin layer 3 is . The perfluorosulfonic acid resin layer 1 is formed by coating a perfluorosulfonic acid resin solution. The modified perfluorosulfonic acid resin layer 3 is formed by coating a perfluorosulfonic acid resin solution to which a doping substance is added, and the doping substance is Pd black, Pt-Ru black, graphene or silicon dioxide commonly used in the art. Example

[0021] 1. Take 700 mL of deionized water and 3560 mL of isopropanol, put the solvent into a three-necked round-bottom flask and mix thoroughly. Weigh 800 g of perfluorosulfonic acid resin powder and add it to the water-alcohol solvent in 4 batches, keep the solution temperature at 30°C, and continue stirring for 50 hours until the resin solution is completely dissolved;

[0022] 2. After the solution in step 1 is prepared, the solution is filtered through a filter cloth and a filter membrane;

[0023] 3. The impregnation solution filtered in step 2 is filtered through an ion exchange resin column to remove metal ions in the impregnation solution to form a perfluorosulfonic acid resin solution;

[0024] 4. Repeat the above steps 1-3, weigh 8.08 g of Pd black particles, add them into the perfluorosulfonic acid resin solution and stir and disperse them for 50 h to form a perfluorosulfonic acid resin solution containing 1 wt.% Pd;

[0025] 5. A PET substrate film with a thickness of 150 μm is installed on a continuous coating device, and then the perfluorosulfonic acid resin solution prepared in step 3 is coated on the surface of the substrate film PET using the process parameters of a coating speed of 0.2 m / min, a coating width of 50 cm, and a scraper feed speed of 12.2 mL / min to form a liquid perfluorosulfonic acid resin layer;

[0026] 6. Place the ePTFE microporous membrane on the active unwinding roller 1, and attach the end of the ePTFE microporous membrane to the surface of the liquid perfluorosulfonic acid resin layer in step 5. After the ePTFE microporous membrane is impregnated, it is placed in a drying oven at 40° C. to form a gel-state ePTFE absorption layer;

[0027] 7. Using a coating blade feed rate of 11 mL / min as a process parameter, the perfluorosulfonic acid resin solution prepared in step 3 is coated on the surface of the gel-state ePTFE absorption layer to form a liquid perfluorosulfonic acid resin layer;

[0028] 8. Place the ePTFE microporous membrane on the second active unwinding roller, and attach the end of the ePTFE microporous membrane to the surface of the liquid perfluorosulfonic acid resin layer in step 7. After the ePTFE microporous membrane is impregnated, it is placed in a drying oven at 40° C. to form a gel-state ePTFE absorption layer;

[0029] 9. Using a process parameter of a scraper feeding speed of 10 mL / min, the perfluorosulfonic acid resin solution containing 1 wt.% Pd black prepared in step 4 is coated on the surface of the gel state ePTFE absorption layer in step 8 to form a liquid modified perfluorosulfonic acid resin layer;

[0030] 10. The gel multilayer composite layer obtained in step 9 is pressed by a pressure roller at a pressure of 2 MPa, and is thoroughly dried at 135° C. to evaporate the solvent, thereby obtaining a multilayer composite proton exchange membrane for DMFC.

[0031] Example 2: 1. Measure 700 mL of deionized water and 3560 mL of isopropanol, and place the solvent in a three-necked round-bottom flask for thorough mixing. Weigh 800 g of perfluorosulfonic acid resin powder and add it to the water-alcohol solvent in 4 batches, keeping the solution temperature at 30°C, and continue stirring for 50 h until the resin solution is completely dissolved;

[0032] 2. After the solution in step 1 is prepared, the solution is filtered through a filter cloth and a filter membrane;

[0033] 3. The impregnation solution filtered in step 2 is filtered through an ion exchange resin column to remove metal ions in the impregnation solution to form a perfluorosulfonic acid resin solution;

[0034] 4. Repeat steps 1-3 above, weigh 24.74 g of Pt-Ru black particles, add them into the perfluorosulfonic acid resin solution and stir and disperse them for 50 h to form a perfluorosulfonic acid resin solution containing 3 wt.% Pt-Ru black;

[0035] 5. A PET substrate film with a thickness of 150 μm is installed on a continuous coating device, and then the perfluorosulfonic acid resin solution prepared in step 3 is coated on the surface of the substrate film PET using the process parameters of a coating speed of 0.2 m / min, a coating width of 50 cm, and a scraper feed speed of 18.3 mL / min to form a liquid perfluorosulfonic acid resin layer;

[0036] 6. Place the ePTFE microporous membrane on the active unwinding roller 1, and attach the end of the ePTFE microporous membrane to the surface of the liquid perfluorosulfonic acid resin layer in step 5. After the ePTFE microporous membrane is impregnated, it is placed in a drying oven at 40° C. to form a gel-state ePTFE absorption layer;

[0037] 7. Using a coating scraper feeding speed of 16.5 mL / min as a process parameter, the perfluorosulfonic acid resin solution prepared in step 3 is coated on the surface of the gel state ePTFE absorption layer to form a liquid perfluorosulfonic acid resin layer;

[0038] 8. Place the ePTFE microporous membrane on the second active unwinding roller, and attach the end of the ePTFE microporous membrane to the surface of the liquid perfluorosulfonic acid resin layer in step 7. After the ePTFE microporous membrane is impregnated, it is placed in a drying oven at 40° C. to form a gel-state ePTFE absorption layer;

[0039] 9. Using a process parameter of a scraper feed rate of 15 mL / min, the perfluorosulfonic acid resin solution containing 3 wt.% Pt-Ru black prepared in step 4 is coated on the surface of the gel state ePTFE absorption layer in step 8 to form a liquid modified perfluorosulfonic acid resin layer;

[0040] 10. The gel multilayer composite layer obtained in step 9 is pressed by a pressure roller at a pressure of 5 MPa, and is thoroughly dried at 135° C. to evaporate the solvent, thereby obtaining a multilayer composite proton exchange membrane for DMFC.

[0041] Example 3: 1. Measure 700 mL of deionized water and 3560 mL of isopropanol, and place the solvent in a three-necked round-bottom flask for thorough mixing. Weigh 800 g of perfluorosulfonic acid resin powder and add it to the water-alcohol solvent in 4 batches, keeping the solution temperature at 30°C, and continue stirring for 50 h until the resin solution is completely dissolved;

[0042] 2. After the solution in step 1 is prepared, the solution is filtered through a filter cloth and a filter membrane;

[0043] 3. The impregnation solution filtered in step 2 is filtered through an ion exchange resin column to remove metal ions in the impregnation solution to form a perfluorosulfonic acid resin solution;

[0044] 4. Repeat steps 1-3 above, weigh 42.1 g of SiO2 particles, add them into the perfluorosulfonic acid resin solution and stir and disperse them for 50 h to form a perfluorosulfonic acid resin solution containing 5 wt.% SiO2;

[0045] 5. A PET substrate film with a thickness of 150 μm is installed on a continuous coating device, and then the perfluorosulfonic acid resin solution prepared in step 3 is coated on the surface of the substrate film PET using the process parameters of a coating speed of 0.2 m / min, a coating width of 50 cm, and a scraper feed speed of 18.3 mL / min to form a liquid perfluorosulfonic acid resin layer;

[0046] 6. Place the ePTFE microporous membrane on the active unwinding roller 1, and attach the end of the ePTFE microporous membrane to the surface of the liquid perfluorosulfonic acid resin layer in step 5. After the ePTFE microporous membrane is impregnated, it is placed in a drying oven at 40° C. to form a gel-state ePTFE absorption layer;

[0047] 7. Using a coating scraper feeding speed of 16.5 mL / min as a process parameter, the perfluorosulfonic acid resin solution prepared in step 3 is coated on the surface of the gel state ePTFE absorption layer to form a liquid perfluorosulfonic acid resin layer;

[0048] 8. Place the ePTFE microporous membrane on the second active unwinding roller, and attach the end of the ePTFE microporous membrane to the surface of the liquid perfluorosulfonic acid resin layer in step 7. After the ePTFE microporous membrane is impregnated, it is placed in a drying oven at 40° C. to form a gel-state ePTFE absorption layer;

[0049] 9. Using a process parameter of a scraper feeding speed of 15 mL / min, the perfluorosulfonic acid resin solution containing 5 wt.% SiO2 prepared in step 4 is coated on the surface of the gel state ePTFE absorption layer in step 8 to form a liquid modified perfluorosulfonic acid resin layer;

[0050] 10. The gel multilayer composite layer obtained in step 9 is pressed by a pressure roller at a pressure of 5 MPa, and is thoroughly dried at 135° C. to evaporate the solvent, thereby obtaining a multilayer composite proton exchange membrane for DMFC.

[0051] Comparative Example 1:

[0052] We purchased Nafion 115 proton exchange membrane from Dupont and conducted physical property tests on the proton exchange membrane, including strength, elastic modulus, swelling rate and proton conductivity.

[0053] Comparative Example 2:

[0054] We purchased Nafion 117 proton exchange membrane from Dupont and conducted physical property tests on the proton exchange membrane, including strength, elastic modulus, swelling rate and proton conductivity.

[0055] Comparative Example 3:

[0056] We purchased Nafion 1110 proton exchange membrane from Dupont and conducted physical property tests on the proton exchange membrane, including strength, elastic modulus, swelling rate and proton conductivity.

[0057] Different from the prior art, the utility model direct methanol fuel cell uses a multilayer composite proton exchange membrane to reduce methanol permeability, improve methanol utilization efficiency, thereby increasing the power density of DMFC, reducing swelling rate, and can achieve mass production of direct coating / roll-to-roll process, ensuring MEA mass production and DMFC output performance, without the need for protonation pretreatment, thereby improving MEA production efficiency.

[0058] The above schematically describes the present invention and its implementation methods, which are not restrictive. The drawings show only one implementation method of the present invention, and the actual structure is not limited thereto. Therefore, if ordinary technicians in this field are inspired by it and design structural methods and embodiments similar to the technical solution without creativity without departing from the purpose of the present invention, they should all fall within the protection scope of the present invention.

Claims

1. A multilayer composite proton exchange membrane for direct methanol fuel cells, It is characterized in that It comprises at least two layers of perfluorosulfonic acid resin layers and ePTFE absorption layers, the perfluorosulfonic acid resin layers and the ePTFE absorption layers are alternately bonded and connected, a modified perfluorosulfonic acid resin layer is bonded under the bottom ePTFE absorption layer, the top perfluorosulfonic acid resin layer serves as the cathode side, and the modified perfluorosulfonic acid resin layer serves as the anode side.

2. The multilayer composite proton exchange membrane for direct methanol fuel cells according to claim 1, It is characterized in that The ePTFE absorption layer is formed by laminating the ePTFE microporous membrane on the fluorosulfonic acid resin layer.

3. The multilayer composite proton exchange membrane for direct methanol fuel cell according to claim 2, It is characterized in that The thickness of the ePTFE absorption layer is .

4. The multilayer composite proton exchange membrane for direct methanol fuel cell according to claim 1, It is characterized in that The thickness of the perfluorosulfonic acid resin layer is .

5. The multilayer composite proton exchange membrane for direct methanol fuel cell according to claim 1, It is characterized in that The thickness of the modified perfluorosulfonic acid resin layer is .

Citation Information

Patent Citations

  • Multilayer gradient composite proton exchange membrane and preparation method thereof

    CN117878365B